Characterisation and use of glass fibre reinforced plastic waste powder as filler in styrene-nutadiene rubber - Ansarifar A; Osmani M; Pappu A; Wang L; Yoong K K (Journal of Rubber Research, 2010)
DL
Keywords: Analytical techniques; Characterisation; Mechanical properties; Recycling; Styrene-butadiene rubber; Waste powder